Characterization of tea-like drink from mangosteen (Garcinia mangostana) pericarp and leaves. - Arcenal, Mara Cheriz B.
Mangosteen pericarp and leaves contain bioactive compounds with antioxidant properties that have tremendous health benefits. Hence, this study characterized a tea-like drink made from oven-dried mangosteen pericarp and leaves and assessed its consumer acceptability. Three tea-like drinks namely: treatment 1 from mangosteen pericarp; treatment 2 from leaves; and treatment 3 from equal parts of pericarp and leaves. Sensory evaluation using rank preference and 9-point hedonic test showed that drinks from mangosteen leaves demonstrate greater sensory acceptability over mangosteen pericarp and the combination of both, hence the most preferred. Compared to a commercial green tea product, the respondents' rankings are relatively equal, indicating that a tea-like drink from mangosteen leaves is comparable to green tea and regarded favorably. Results from phytochemical screening showed that all tea-like drinks contain tannins, saponin, and flavonoids. The total phenolic content is 188.48 mg GAE/100 mL for the pericarp, 127.09 mg GAE/100 mL for leaves, and 157.58 mg GAE/100 mL for the pericarp and leaves combination. All tea-like drinks showed high inhibition (86-90%) against DPPH-radical scavenger indicating a high ability to counteract oxidative stress caused by free radicals. Furthermore, results from the proximate analysis showed that the dried mangosteen pericarp has lower moisture content (6.27%), ash (2.71%), and protein content (2.81%) than dried mangosteen leaves (moisture content: 7.4%; ash: 4.75%; protein content: 7.09%). In Brine Shrimp Assay test, probit analysis shows that LC50 (the concentration that causes 50% death of the brine shrimp) of mangosteen pericarp is 5.760 ppm and 96.582 ppm for leaves. Thus, both mangosteen pericarp and leaves showed signs of toxicity against brine shrimp but this has no direct relationship to toxicity with humans. Overall, this study affirms the potential utilization of mangosteen leaves and pericarp in developing a tea-like drink.